(untitled) (International Scientific Journal Alfraganus, 2024)
It is known that labor discipline is an objective necessity in the production process. In the legal literature, this concept has been interpreted in different ways. Labor discipline is a procedure that determines the interaction of the participants in production, strengthened by legal norms. More simply, labor discipline refers to the necessity of joint labor as well as the subordination of Labor participants to a certain order. Labor discipline is studied as a subject of various disciplines. In the field of law, however, it is studied and researched as a legal category. labor discipline is also important as an institution of labor law. This aspect of it is manifested as a system of legal norms that regulate the rules of the internal Labor procedure of the enterprise, the duties of the employee and the employer, as well as establishing honest labor and measures to stimulate it, and the disciplinary responsibility of employees for violation of labor discipline. labor discipline by its nature is also, to a certain extent, a mirror of the true behavior and morality of the employee. Because, in this sense, it testifies to the production discipline of the employee and to what extent he adheres to the established order in this regard. This article analyzes all the circumstances related to the labor discipline of employees of enterprises and institutions through legal norms in Uzbekistan. Already, the state of labor productivity in production is largely directly related to whether employees adhere to labor discipline in the labor process or not.